Genesis of self-identity as DisOther: Life histories of people who stutter - Harsha Kathard (South African Journal of Communication Disorders, 2004)
This paper explores the processes shaping self-identity formation as DisOther and the actions of participants who stutter. It illuminates the experiences of adults who stutter using a biographical, narrative, life history methodology. The participants were seven South African adults of diverse racial, social and economic backgrounds from KwaZulu-Natal, South Africa. Five males and two female were invited to participate via purposive and convenience sampling processes. Their stories of living with stuttering in their life worlds over time were constructed via biographical interviews using personal, social and temporal lenses typical of life history methodology. The interviews were audio-recorded and transcribed. The data were analysed at two levels using a combination of strategies. The first level entailed a narrative analysis that was represented as research stories for each participant. The cross-case and thematic analysis of research stories constituted the second level analysis of narratives. The findings explain the complex and interrelated personal and social processes over time which contribute to the genesis of self-identity formation as DisOther. Social inscriptions of difference occurred in immediate home, school and work contexts over time via multiple processes such as labelling, norming, judging and teasing. Personal processes included discoveries of difference via critical events, repeated reinforcement of difference, self-judgement and temporal burdening. Furthermore, the actions participants took in negotiating stuttering were examined. The implications of the findings and limitations of the study are presented.